2018
DOI: 10.1371/journal.pone.0205356
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of PCR primers for the detection of occult hepatitis B virus infection in Mexican patients

Abstract: BackgroundOccult hepatitis B infection (OBI) is defined as the presence of hepatitis B virus (HVB) DNA in the liver of HBsAg negative individuals with or without detectable viral DNA in serum. OBI is a diagnostic challenge as it is characterized by a very low viral load, intermittently detectable through time. Individuals with OBI can develop chronic hepatic disease, including liver cirrhosis and hepatocellular carcinoma. The aim of this work was to produce tools to improve OBI detection of the HVB genotypes p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 31 publications
(34 reference statements)
0
11
0
Order By: Relevance
“…The association of OBI with hepatocarcinogenesis has been reported 4,10‐12 . In an analysis of 53 HBsAg‐negative patients with unexplained HCC, Wong et al reported that cccDNA was detected in liver tissue of 29 (47%) patients 13 .…”
Section: Discussionmentioning
confidence: 99%
“…The association of OBI with hepatocarcinogenesis has been reported 4,10‐12 . In an analysis of 53 HBsAg‐negative patients with unexplained HCC, Wong et al reported that cccDNA was detected in liver tissue of 29 (47%) patients 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Core and S/pol regions were evaluated for detecting HBV DNA in qualitative PCR. These two HBV targets are frequently used in commercial assays to detect HBV in serum (Abbott RealTime HBV Assay and the Cobas TaqMan HBV test, version 2; Liu et al, 2019) and are employed for detecting occult HBV or acute cases (Liu et al, 2019; Sosa‐Jurado et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The association of OBI with hepatocarcinogenesis has been reported. 3,[8][9][10] In an analysis of 53 HBsAgnegative patients with unexplained HCC, Wong et al reported that cccDNA was detected in liver tissue of 29 (47%) patients. 11 On the basis of these reports, it was presumed that our patient also likely developed carcinogenesis from OBI.…”
Section: Discussionmentioning
confidence: 99%